2015
DOI: 10.1371/journal.pone.0131892
|View full text |Cite
|
Sign up to set email alerts
|

Correction: A RNA-Seq Analysis of the Rat Supraoptic Nucleus Transcriptome: Effects of Salt Loading on Gene Expression

Abstract: There are a number of errors in the captions for S1 to S9 Fig Step 1, "Sequence Adaptor Clipping". Read pairs, 101bp in length, were adaptor clipped via FASTQ/A Clipper (http://hannonlab.cshl.edu). Broken read pairs as a result of clipping were discarded.Step 2, "Sequence Quality Inspection". Intact read pairs remaining post-clipping were import into CLCbio and the "Create Sequencing QC Report" tool used to generate one report per sample. These reports, each containing per-sequence and per-base quality statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Would this be sufficient to ensure the maintenance of the stimulus-secretion coupling when the MNCs are exposed to a long period (hours to days) of hyperosmotic challenge, such as during prolonged water deprivation or salt-loading? As we discuss in the coming sections, under chronic dehydration, the MNCs experience dramatic transcriptomic remodeling, which includes changes in the expression of several genes encoding plasma membrane channels and transporters ( Hindmarch et al, 2006 ; Greenwood M. P. et al, 2015 ; Johnson et al, 2015 ; Pauža et al, 2021 ). Another important adaptation is the increased complexity of the cytoskeleton array observed during sustained hyperosmolality ( Barad et al, 2020 ; Hicks et al, 2020 ), whose crucial role for osmosensitivity was previously demonstrated by Prager-Khoutorsky et al (2014) , also discussed later in this review.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Would this be sufficient to ensure the maintenance of the stimulus-secretion coupling when the MNCs are exposed to a long period (hours to days) of hyperosmotic challenge, such as during prolonged water deprivation or salt-loading? As we discuss in the coming sections, under chronic dehydration, the MNCs experience dramatic transcriptomic remodeling, which includes changes in the expression of several genes encoding plasma membrane channels and transporters ( Hindmarch et al, 2006 ; Greenwood M. P. et al, 2015 ; Johnson et al, 2015 ; Pauža et al, 2021 ). Another important adaptation is the increased complexity of the cytoskeleton array observed during sustained hyperosmolality ( Barad et al, 2020 ; Hicks et al, 2020 ), whose crucial role for osmosensitivity was previously demonstrated by Prager-Khoutorsky et al (2014) , also discussed later in this review.…”
Section: Introductionmentioning
confidence: 99%
“…To summarize the data related to the expression of membrane transporters and channels in the SON in response to prolonged hyperosmolality in rats, we have integrated data from four publications revealing new possible players in the regulation of MNCs’ electrophysiological response. While Hindmarch et al (2006) and Greenwood M. P. et al (2015) used the microarray technology to analyze the SON transcriptomic response, Johnson et al (2015) and Pauža et al (2021) took advantage of the next generation RNAseq technique. Furthermore, Hindmarch et al (2006) and Pauža et al (2021) used 3 days of water deprivation to stimulate the SON, while Johnson et al (2015) used 5 days of salt loading (hypertonic saline as the only fluid available), and Greenwood et al ( Greenwood M. P. et al, 2015 ) compared the SON transcriptomic response to 3 days of water deprivation or 7 days of salt loading.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations